2014
DOI: 10.1021/ac502478a
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for Photophysical Processes and Specific Signal Intensity Changes in Fluorescence-Detected Sedimentation Velocity

Abstract: Fluorescence detected sedimentation velocity (FDS-SV) has emerged as a powerful technique for the study of high-affinity protein interactions, with hydrodynamic resolution exceeding that of diffusion-based techniques, and with sufficient sensitivity for binding studies at low picomolar concentrations. For the detailed quantitative analysis of the observed sedimentation boundaries, it is necessary to adjust the conventional sedimentation models to the FDS data structure. A key consideration is the change in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…For example, for rsEGFP with a scanning beam of 13 mW we measure a depletion rate of 5.08 [4.97–5.19; 95% CI]×10 –4 /sec, approaching a final fluorescence of 13.4 [13.0–13.9; 95% CI]% its initial value, associated with a particle sedimentation coefficient of 2.50 [2.45–2.54; 95% CI] S and apparent molar mass of 29.5 [26.5–33.0; 95% CI] kDa. By contrast, as previously established ( Zhao et al, 2014b ), no photophysical processes are detectable under this illumination for other fluorophores such as fluorescein-based DL488 ( Figure 2b ) and standard EGFP.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…For example, for rsEGFP with a scanning beam of 13 mW we measure a depletion rate of 5.08 [4.97–5.19; 95% CI]×10 –4 /sec, approaching a final fluorescence of 13.4 [13.0–13.9; 95% CI]% its initial value, associated with a particle sedimentation coefficient of 2.50 [2.45–2.54; 95% CI] S and apparent molar mass of 29.5 [26.5–33.0; 95% CI] kDa. By contrast, as previously established ( Zhao et al, 2014b ), no photophysical processes are detectable under this illumination for other fluorophores such as fluorescein-based DL488 ( Figure 2b ) and standard EGFP.…”
Section: Resultssupporting
confidence: 75%
“…The psFPs make up a class of fluorescent proteins that can be actively switched between fluorescent and non-fluorescent states using different wavelengths of illumination. While they have been engineered for entirely different purposes in nanoscience and fluorescence imaging, we have previously observed that under the illumination conditions of FDS-SV they are induced to slowly switch by virtue of the excitation light when radially scanning the spinning sample ( Zhao et al, 2014b ). Even though the mechanism of photoswitching in psFPs generally may involve multiple states, in the low-power exposure that occurs during sedimentation using the FDS the process is quantitatively modeled very well as a single exponential.…”
Section: Introductionmentioning
confidence: 99%
“…The above difficulties can be easily overcome by careful design and performance of the experiments and associated data analysis, leading to truly exceptional results (Zhao et al 2014a;Chaturvedi et al 2017a). It has been shown previously that, due to the large number of data points acquired during a typical SVexperiment, meaningful results can be derived even when boundary amplitudes are comparable with the stochastic noise of the data acquisition (Zhao et al 2012).…”
Section: Auc-fdsmentioning
confidence: 99%
“…The approach is very general, and without any further complications refinements on χ 1, nd are possible to account for solvent compressibility, 51 time-varying centrifugal fields, 52 , the finite scanning speed of the scanning systems, 3 optical signal magnification gradients, 53 or spatiotemporal modulation of signal increments in fluorescence detection. 54 …”
Section: Theorymentioning
confidence: 99%